BAKTERI AEROB DAN UJI KEPEKAAN ANTIMIKROBA - Erviani Zuhriah; Nurhayana Sennang; Darmawaty ER (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Nosocomial infection is an infection acquired in hospitals, which occur more frequently in poor and developing countries such as Indonesia, one percent of the related cases leads to death. The occurrence of nosocomial infection causes the lengthening of hospitalization and increased risk of disease transmission. According to Permenkes No. 1204/Menkes/SK/X/2004, the Emergency Room is one of the high-risk areas. The objectives of this research were to quantify the number of aerobic bacteria, to know the identification method of the pathogenic bacteria and to determine the antimicrobial sensitivity pattern in the emergency installation. A cross sectional study was performed by collecting air samples at eleven treatment rooms of the Emergency installation in dr. Wahidin Sudirohusodo Hospital Makassar by using Microbiology Air Sampler 100 (MAS 100). The bacterial identification and antimicrobial susceptibility tests (AST) were conducted at the Balai Besar Laboratorium Kesehatan Makassar (July to September 2009). The number of bacterial colonies were 288–6570 CFU/m3. Pathogenic bacteria identified in the study were Stomatococcus mucilaginous, Staphylococcus haemolyticus and Acinetobacter calcoaceticus, which were still sensitive to tetracycline and resistant to ceftazidim and kanamycin.The number of bacterial colonies exceeded the standard number established by the Decree of Indonesian Health Minister